Risk Factors for Lung Function Disorders in Craftsmen of Mattress Made of Textile Waste in Banjarkerta Purbalingga Year 2011 - Budi Utomo; Lagiono Lagiono; Nur Hilal (Jurnal LINK, 2012)
Banjarkerta, a village in district Karanganyar, Purbalingga, is a central village of mattress craftsman with textile waste materials as a substitute for cotton. One of negative impacts in consequence of work for the craftsmen is lung function disorder, which is caused by dust of textile waste. The other risk factors are age, work period, Body Mass Index, use of masks, smoking habits, and history of pulmonary disease.The purpose of this study was to find out the risk factors for lung function disorder in craftsmen of mattress in Banjarkerta, Purbalingga, year 2011.This research was conducted with cross sectional approach, observing 85 respondents, using random sampling techniques. The data collected was obtained by measurements (dust variables, BMI, lung capacity) and interviews (age variables, gender, work period, smoking behavior, and history of pulmonary disease). The collected data is then presented in tabular and narrative. The data analysis is done by analyzing tables and cross-table analysis, using the calculation of Ratio Prevalence  (RP).The results of this study is that there is lung function disorder in mattress craftsman, with the normal criteria (23.5%), the only restriction or obstruction (15.3%), the combined restriction and obstruction (61.2%). Factors associated with lung function disorder are age (RP = 1,220); gender (RP = 3.137); working hour (RP = 1,333); the custom of wearing masks (RP = 1.319) and a history of pulmonary disease (RP = 1.502). Factors not associated with risk of lung function disorder are work period (RP = 0.611);, BMI (RP = 0.807 and smoking habits; (RP = 0.583). Indoor levels of airborne dust in the home industry (26,656 and 80,000 ìg/Nm3 ìg/Nm3), already far exceeds the Threshold Limit Value (TLV) which allowed for the air space of industry, that is 10,000 ìg/Nm3.  Researchers gave suggestions for the craftsmen to wear a mask that is good and right, and to get occupational health monitoring by the Health Center / Department of Health.